Perancangan Sistem Informasi Penerimaan Siswa Sepak Bola Berbasis Web - Abdul Hasbi; Riswal Hanafi Siregar (CV. Multi Kreasi Media, 2024)
Parung Men's Football School which is located on Jl. Pan Gas No. 7, Pemagarsari, Kec. Parung, Bogor Regency, West Java 16330 is a football school service business that carries out its business processes in a conventional way where prospective students must come to the Parung Men's Soccer School to register and take a student acceptance test. In addition, the processing of student data and test data is also done manually, so that data loss often occurs which will complicate the preparation of student admission reports at the end of the period. Under these conditions, of course, the Parung Men's Football School has not yet used internet media which can help satisfy registrants who will register other than as a promotional medium for Parung Men's Football School. The system development method used in this research is web engineering, which is a software engineering model used for developing web-based applications. With a web-based computerized system that can help make it easier for staff and owners to control registrants on a daily basis, the registration information system for the Parung Men's Soccer School is urgently needed because it can be used as a promotional medium.